The Influence of Patriarchal Culture and its Obstacles in a Case Study of Women's Rights Struggle for Provincial Legislative Council Chair in Bener Meriah Regency, Central Aceh - Andita Oktaviani; Delya Anandiesti; Efrida Primani; Natigor Kabinet; Aniqotul Ummah (Journal of Feminism and Gender Studies, 2025)
Various lives in society can greatly influence many aspects and fields in Indonesia. One of them is the patriarchal culture which is deeply rooted and influences the lives of women as one of the groups who are always looked down upon and always placed under men. Society considers that women do not have special abilities above men and cannot do many things without men. But the reality is that women can do more than society can imagine. The discussion of the case study above proves that there were minimal wins for women in the election of legislative candidates in the DPRK seat of Bener Meriah Regency in 2019. This district, which is still in the shackles of patriarchy, is trying to increase women's participation in political life even though in the end it still lost the election of its legislative candidates in 2019. This proves that patriarchal culture is still inherent in Indonesia and requires legal reform from the government to help voice the rights of women who want to sit in legislative seats and government agencies.